Project 9 : The Birth of the Air Commandos in World War II - Okerstrom, Dennis R. (American military experience series., 2014)
Project 9: The Birth of the Air Commandos in World War II is a thoroughly researched narrative of the Allied joint project to invade Burma by air. Beginning with its inception at the Quebec Conference of 1943 and continuing through Operation Thursday until the death of the brilliant British General Orde Wingate in March 1944, less than a month after the successful invasion of Burma, Project 9 details all aspects of this covert mission, including the selection of the American airmen, the procurement of the aircraft, the joint training with British troops, and the dangerous night-time assault behind Japanese lines by glider. Based on review of hundreds of documents as well as interviews with surviving Air Commandos, this is the history of a colorful, autonomous, and highly effective military unit that included some of the most recognizable names of the era. Tasked by the General of the Army Air Forces, H. H. "Hap" Arnold, to provide air support for British troops under the eccentric Major General Wingate as they operated behind Japanese lines in Burma, the Air Commandos were breaking entirely new ground in operational theory, tactics, and inter-Allied cooperation. Okerstrom's in-depth research and analysis in Project 9 shed light on the operations of America's first foray into special military operations, when these heroes led the way for the formation of modern special operations teams such as Delta Force and Seal Team Six.